Wealth Dynamics in the 1980's and 1990's: Sweden and the U.S. - Anders Klevmarken; Joseph Lupton; Frank Stafford (Uppsala University, Department of Economics, 2000)
Given differences in public saving programs between Sweden and the United States, an examination of household private wealth accumulation in these two countries can be enlightening. In this paper we examine wealth inequality and mobility in Sweden and the United States over the past decade. We show that wealth inequality has been significantly greater in the U.S. than in Sweden and, while remaining relatively constant since the mid-1980s in Sweden, has increased in the United States. In addition to less inequality and a higher median wealth, we also show that wealth quintile mobility in the 1990s has been 25.7% higher in Sweden, as measured by Shorrocks index. Noting the role of various demographic components in shaping the patterns of wealth mobility as well as the importance of the initial wealth distribution, we utilize a matching algorithm that controls for these differences. Matching on the initial wealth distribution alone accounts for most of the mobility difference between the two countries and yields a Shorrocks index in the U.S. 11.1% less than that in Sweden. Adjusting for the large degree of imputation in the Swedish data, the U.S. index is only 3.4% to 6.1% less than that of Sweden. Along with exploring the role of racial composition differences, we conclude tha demographic variation between Sweden and the U.S. play very little role in explaining wealth mobility beyond that explained by the initial wealth distribution. Despite the higher quintile mobility in Sweden, dollar mobility is still high in the United States.
urn:nbn:se:uu:diva-2499
Keywords: C15; D31; 330; Mobility; Wealth; Panel data; Statistical matching; Comparison U.S. - Sweden; Vermögen; Privater Haushalt; Vermögensverteilung; Vergleich; USA; Schweden